2001
DOI: 10.1096/fj.00-0487fje
|View full text |Cite
|
Sign up to set email alerts
|

Lack ofp53accelerates hepatocarcinogenesis in transgenic mice constitutively overexpressing c‐mycin the liver

Abstract: The role of the tumor suppressor function of p53 in the process of hepatocellular carcinoma (HCC) development is still enigmatic in view of uncertainties with respect to the phenotype of most p53 mutations found in human HCCs. We therefore analyzed the effect of the p53 knockout (p53KO) genotype, which imparts a clear‐cut loss of function, on hepatocarcinogenesis in livers of transgenic mice prone to develop this tumor type. Deterministic HCC formation in mice overexpressing transgenes encoding murine c‐myc, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…We found by PCR that tumors did not generally inactivate the second allele through deletion (Figure 10E). Our results extend previous findings that suggest that the lack of p53 function cooperates with MYC to induce HCC (Klocke et al 2001). We conclude that even a slight reduction of p53 function greatly facilitates the ability of MYC to induce tumorigenesis in adult hepatocytes.…”
Section: Resultssupporting
confidence: 91%
“…We found by PCR that tumors did not generally inactivate the second allele through deletion (Figure 10E). Our results extend previous findings that suggest that the lack of p53 function cooperates with MYC to induce HCC (Klocke et al 2001). We conclude that even a slight reduction of p53 function greatly facilitates the ability of MYC to induce tumorigenesis in adult hepatocytes.…”
Section: Resultssupporting
confidence: 91%
“…Since DLC1-deficient mice dies at embryonic stage, it would be interesting to see if hepatocyte-specific deficiency of DLC1 may predispose such mice to the development of HCC and to delineate the role of DLC2 deficiency in the development of HCC in these mice. It was demonstrated that loss of p53 would accelerate hepatocarcinogenesis in transgenic mice overexpressing c-myc [29]. It would be informative to cross DLC2-deficient mice with other knockout mice of tumor suppressor genes, such as p53 and/or transgenic mice overexpressing oncogenes such as c-myc and TGF-alpha [30].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, lack of the molecular gatekeeper p53 accelerates HCC in c-MYC tg in the liver [28]. Enhanced tumor growth, pronounced malignant structure and an invasive growth pattern correlated with p53-deficiency in livers of alb-Cre + /c-MYC tg .…”
Section: Deconstructing C-myc: Transgenic Modelsmentioning
confidence: 99%